PERLINDUNGAN HUKUM TERHADAP KONSUMEN AKIBAT PRODUK KECANTIKAN YANG MEMPUNYAI EFEK SAMPING TERHADAP KULIT - Maharani, Raden Bella Bintang; Rahmatiar, Yuniar; Abas, Muhamad (JURNAL LEGISIA, 2024)
In this era, beauty products are important for building self-confidence for women and men. Beauty products must also contain ingredients that are safe for the skin so that the skin looks healthy. However, in reality, some beauty products contain dangerous ingredients that can cause side effects on the skin. These ingredients contain hydroquinone, mercury, paraben, formaldehyde, phthalates, and triclosan. If used for a long time, it can cause skin problems such as itchy skin, excessive acne, blisters on the skin, blackened areas of the skin (ochronosis), and pose various risks to body health. Meanwhile, it has been explained in RI POM Regulation No. 23 of 2019 regarding raw materials that may be used in beauty products, of course, they must contain safe, quality, and beneficial ingredients. This research discusses legal protection for consumers due to products that cause side effects on the skin. What is the legal protection for consumers who cause side effects on the skin? Consumers must be given special protection for the content information listed on beauty products or packaging. Resolving consumer protection regarding the consequences of beauty products containing side effects on the skin can be done through legal action. Resolving consumer protection regarding the consequences of beauty products containing side effects on the skin can be done through legal action. This legal effort can be made to make claim for compensation or report it tothe athorities or police.